Hyssopus Essential Oil: An Update of Its Phytochemistry, Biological Activities, and Safety Profile. (13th January 2022) - Sharifi-Rad, Javad; Quispe, Cristina; Kumar, Manoj; Akram, Muhammad; Amin, Mewish; Iqbal, Mehwish; Koirala, Niranjan; Sytar, Oksana; Kregiel, Dorota; Nicola, Silvana; Ertani, Andrea; Victoriano, Montserrat; et al.
Abstract : The genus Hyssopus is widespread in central Asia, East Mediterranean, and Mongolian areas. It has six main species which are used as herbal remedies, such as Hyssopus officinalis which is used as a condiment and flavoring agent in food industry. The other five species are H. ambiguus, H. cuspidatus, H. latilabiatus, H. macranthus, and H. seravschanicus . Its species are used in the treatment of various ailments such as cold, cough, loss of appetite, fungal infection, and spasmodic condition. Its constituents especially essential oils are popularly used as an additive in beverages, foods, and cosmetics. The volatile constituents are used for aroma in the food industry, cosmetic industry, and household products. The important active constituents in its essential oils are β -pinene, pinocamphone, isopinocamphone, and other terpenoids. Hyssopus genus is also bundled with other secondary metabolites including flavonoids luteolin, quercetin, apigenin, and their glucosides, as well as phenolic compounds including ferulic, p -hydroxy-benzoic acid, protocatechuic acid, chlorogenic, and caffeic acid. Combinedly, the extracts of Hyssopus are reported to have potential antiviral and antifungal activities proven using in vitro studies, whereas in vivo investigations have reported the crucial role of Hyssopus extracts in plasma membrane relaxation, cytotoxic, and sedative effects. This plant is believed to be relatively safe at levels commonly used in foods; nevertheless, more studies are needed to determine the safety profile.